IDENTIFIKASI PERILAKU IBU DALAM PEMBERIAN MP-ASI DINI DI PUSKESMAS TAMBANG KABUPATEN KAMPAR - Donna Febri Rotua; Riri Novayelinda; Wasisto Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Early complementary feeding is giving food or drink to infants less than 6 months. This study aims to identify the mother's behavior in giving of early complementary feeding at Puskesmas Tambang Kabupaten Kampar. This research uses quantitative research type with descriptive design. Subject selection technique in this study using total sampling by taking all respondents as much as 81 respondents. Data collection used questionnaire related to mother’s behavior in early complementary feeding with recall method. The results of this study indicate the mother's behavior in the provision of early breastfeeding, covering the age of the infant was first given early complementary feeding ie 5 - <6 months as many as 23 mothers (28.4%), the type of early complementary feeding mixed (local and artificial) as many as 33 mothers (40.7%), the texture of early complementary feeding giving the most is crushed texture of 76 mothers (93.8%), the frequency of giving of early complementary feeding every week is category of always (every day) as much as 42 mothers (51,9%), amount of early complementary feeding giving every week with the category of many 41 mothers (50.6%), the the reason for breastfeeding are not sufficient as much as 72 mothers (88.9%), infant health problem which often happened is cough as much as 32 baby (39,5 %). Recommendation in this research is practical action through approach with health counseling to mother about the danger of early complementaryKeywords: Early complementary feeding, identification, and mother's behavior.